ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL PADA MATERI GETARAN DAN GELOMBANG DI KELAS VIII MTs NEGERI 1 PALANGKA RAYA - Ega Dyah Pratiwi; Saulim DT Hutahaean; Andi Bustan; Pri Ariadi Cahya Dinata (Journal of Banua Science Education, 2022)
Teaching and learning process are intended to give optimum transformation to student’s knowledge. Hence, assessment process revealed students not always success to reach targeted learning outcomes. Therefore, this research was conducted to determine students’ resistance in learning and solving wave and vibration questions. The type of this research is pre-experimental with one shot case study design. The samples were students of eighth class consist of 32 students. The data collecting instrument was 25 multiple choicle questions as learning outcomes test. Based on the result, it can be determined: (1) students who completed individually as many as 5 people out of 24 students. (2) classical completeness is only obtained by 21% of students who have completed so that they have not reached the standard of completeness. (3) TPK com-pleteness for cognitive THB was 2 TPK (17%) of the total TPK. (4) The percentage of difficulty in the C2 aspect for difficulties in explaining concepts is 20.14% with very low difficulty criteria. (5) The percentage of students' difficulty in the C3 aspect for unit conversion difficulty is 56.55% with moderate difficulty criteria, writing formulas is 34.52% with low difficulty criteria, arithme-tic operations are 52.38% with moderate difficulty criteria and the final answer is 63.10%. The percentage of students' difficulty in the C4 aspect for unit conversion difficulty is 62.50% with high difficulty criteria, writing formulas is 45.83% with moderate difficulty criteria, arithmetic operations are 58.33% with moderate difficulty criteria and the final answer is 100%.Keywords: Resistance of physics questions solving, students’ learning outcomes, wave and vibra-tion. ABSTRAKKegiatan belajar mengajar diharapkan dapat memberikan perubahan pengetahuan yang optimal bagi siswa. Namun, proses pengukuran mengungkapkan bahwa siswa-siswa tidak selalu mencapai hasil belajar yang ditargetkan. Oleh karena itu, penelitian ini dilakukan untuk mengetahui kesulitan dalam belajar dan memecahkan soal-soal getaran dan gelombang. Jenis penelitian ini adalah penelitian Pre-Experimental menggunakan desain one shot case sttudy. Sampel pada penelitian ini adalah kelas VIII-2 dengan jumlah 32 siswa. Instrument yang digunakan dalam penelitian ini adalah soal Tes Hasil Belajar (THB) pilihan ganda yang berjumlah 25 soal. Berdasarkan hasil penelitian diperoleh; (1) siswa yang tuntas secara individu sebanyak 5 orang dari 24 siswa, (2) ketuntasan secara klasikal hanya diperoleh 21% siswa yang tuntas sehingga belum mencapai standar ketuntasan, (3) ketuntasan TPK untuk THB kognitif sebanyak 2 TPK (17%) dari keseluruhan TPK, (4) persentase kesulitan aspek C2 untuk kesulitan menjelaskan konsep sebesar 20.14% dengan kriteria kesulitannya sangat rendah, (5) persentase kesulitan siswa pada aspek C3 untuk kesulitan konversi satuan sebesar 56,55% dengan kriteria kesulitan sedang, menuliskan rumus sebesar 34,52% dengan kriteria kesulitan rendah, operasi hitung sebesar 52.38% dengan kriteria kesulitan sedang dan jawaban akhir sebesar 63.10%. Persentase kesulitan siswa pada aspek C4 untuk kesulitan konversi satuan sebesar 62.50% dengan kriteria kesulitan tinggi, menuliskan rumus sebesar 45.83% dengan kriteria kesulitan sedang, operasi hitung sebesar 58.33% dengan kriteria kesulitan sedang dan jawaban akhir sebesar 100%.Kata kunci: Getaran dan gelombang, hasil belajar, kesulitan penyelesaian soal fisika.